Research progress on free fatty acid receptors and bronchial asthma - Fangxin Cao; Na Lin; Juntao Lin; Gai Yang; Xintong Wang (Alergologia Polska)
Bronchial asthma is a chronic respiratory disease characterized by reversible airflow limitation, including airway hyperresponsiveness, airway inflammation and airway remodeling. The clinical manifestations are recurrent tachypnea, wheezing, dyspnea, cough and other manifestations, which seriously affect the life of patients. The incidence of asthma increases the social and economic burden. Many researchers have reported the role of free fatty acid receptors (FFARs) in diseases such as bronchial asthma, colitis, arthritis and other diseases. Free fatty acids are ligands of FFARs. GPR40, GPR41, GPR43, GPR120 and GPR84 have been identified as FFARs. There are many studies on fatty acids and asthma. However, whether this represents the role of FFARs needs further study. FFARs can affect the occurrence and progression of asthma through β-arrestins, RhoA/ROCK1, PLC/IP3, MAPK, AMPK and other pathways. This article reviews the research progress on the role of FFARs in bronchial asthma, with the aim of providing a reference for their use as new targets for the treatment of bronchial asthma.